2017
DOI: 10.1007/978-3-319-64519-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Direct TS-Wave Simulation on a Laminar Wing-Profile with Forward-Facing Step

Abstract: Arbeitsgemeinschaft) founded towards the end of the 1970s, whereas DGLR is the German Society for Aeronautics and Astronautics (Deutsche Gesellschaft für Luftund Raumfahrt -Lilienthal Oberth e.V.).The mission of STAB is to foster aerodynamics research and its appreciation in Germany. This is accomplished by creating vivid forums for scientific discussions and by disseminating most recent research results, thereby enhancing scientific progress and avoiding unnecessary duplication in research work. Particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Later studies (Béguet et al (2016) and Costantini et al (2015)) suggested using local flow p roperties and relative defect dimensions with respect to the local boundary layer thickness instead; however, use of Nenni and Gluyas criteria can still be found today because of its simplicity, a decisive factor of usability in the aerospace industry. Since then, numerous investigations, both experimental (e.g., Klebanoff and Tidstrom (1972), Dovgal et al (1994), Wang and Gaster (2005) or Rius-Vidales and Kotsonis (2020)) and numerical (e.g., Perraud et al (2005), Rizzetta and Visbal (2014) or Lüdeke and Backhaus (2018)) were carried out to further understand the physics involved in the onset of laminar-turbulent transition induced by surface defects. However, the complexity of most numerical models does not currently allow to consider this approach as part of the design process.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies (Béguet et al (2016) and Costantini et al (2015)) suggested using local flow p roperties and relative defect dimensions with respect to the local boundary layer thickness instead; however, use of Nenni and Gluyas criteria can still be found today because of its simplicity, a decisive factor of usability in the aerospace industry. Since then, numerous investigations, both experimental (e.g., Klebanoff and Tidstrom (1972), Dovgal et al (1994), Wang and Gaster (2005) or Rius-Vidales and Kotsonis (2020)) and numerical (e.g., Perraud et al (2005), Rizzetta and Visbal (2014) or Lüdeke and Backhaus (2018)) were carried out to further understand the physics involved in the onset of laminar-turbulent transition induced by surface defects. However, the complexity of most numerical models does not currently allow to consider this approach as part of the design process.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies (Béguet et al (2016) and Costantini et al (2015)) suggested using local flow properties and relative defect dimensions with respect to the local boundary layer thickness instead; however, use of Nenni and Gluyas criteria can still be found today because of its simplicity, a decisive factor of usability in the aerospace industry. Since then, numerous investigations, both experimental (e.g., Klebanoff and Tidstrom (1972), Dovgal et al (1994), Wang and Gaster (2005) or Rius-Vidales and Kotsonis (2020)) and numerical (e.g., Perraud et al (2005), Rizzetta and Visbal (2014) or Lüdeke and Backhaus (2018)) were carried out to further understand the physics involved in the onset of laminar-turbulent transition induced by surface defects. However, the complexity of most numerical models does not currently allow to consider this approach as part of the design process.…”
Section: Introductionmentioning
confidence: 99%
“…Within different EU-projects, such as Clean Sky I and II, suction through a porous leading edge of a vertical-tail plane (VTP) is investigated by wind tunnel tests and numerical analysis [2,12]. As mentioned, the 2D TS-wave character allows simplified DNS of the flow field using a well-validated high-order numerical approach [13,14] which is used for a detailed simulation of transitional modes in the region of interest.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate sufficient transition suppression by the suction panel with or without welding of the neighbor panel, direct numerical simulations of critical TS-modes are carried out here [14], including post-processing and comparison with growth rates on unperturbed surfaces and stabilization by uniform suction. The strong stabilizing effect of such suction techniques was already calculated by Rist and Zahn [2,15], using DNS and LST approaches.…”
Section: Introductionmentioning
confidence: 99%